ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RESPON KONSUMEN PADA PRODUK MIE INSTAN INDOFOOD DI HYPERMARKET GIANT PANAM PEKANBARU - Maulana, Imam Agung; Othman, Lie (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The ritels Development modern to give it more many choices expensy place for consumer. Besides minimarket and supermarket, hypermarket is one of ritels type modern who be loved because some its superiorities. From various the stuff that to be traded, Noodle product Instan Indofood is one of food product that can be bought in Giant hypermarket. Quality, quality also product kontinuitas availableness Instan Indofood Noodle is important matter in his management. his Operation with optimal cost, is important step for management side hypermarket to to reach effectivity also .Aim from research this is to to know the factors that to influence response to Noodle Product Instan Indofood Giant Hypermarket Pekanbaru.As for this research is done in giant Hypermarket panam pekanbaru , whereas research object is noodle product instan Indofood that in pasrkan in giant hypermarket pekanbaru.From writer research result to conlude it from fourth research variable according to entirely be told good, from reaction responden tell that instans noodle is to be liked by all circleGiant Hypermarket Pekanbaru Panam to be suggested to arrest it quality and volume /noodle content instan Indofood.key Word: Marketing, Ritel , Consumers Response